2010
DOI: 10.1097/ncc.0b013e3181d86739
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of Visualization and Acupuncture on the Quality of Life of Adult Cancer Patients Receiving Chemotherapy

Abstract: Adults with cancer are able to choose between involvement or not with this kind of CAM intervention. Global health could be improved by participating in this type of intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
0
13
1
3
Order By: Relevance
“…Patients with stomach or rectum cancer had higher symptoms. Different studies, contrary to the present study, have reported that cancer type has no effect on life quality (Sawada et al, 2009;van den Beuken-van Everdingen et al, 2009). …”
Section: Eortc Qlq C-30 Scorescontrasting
confidence: 99%
“…Patients with stomach or rectum cancer had higher symptoms. Different studies, contrary to the present study, have reported that cancer type has no effect on life quality (Sawada et al, 2009;van den Beuken-van Everdingen et al, 2009). …”
Section: Eortc Qlq C-30 Scorescontrasting
confidence: 99%
“…Sawada et al . [44] found that acupuncture during chemotherapy induced a better quality of life in patients.…”
Section: Discussionmentioning
confidence: 99%
“…As características sócio-demográficas e clínicas encontradas neste estudo foram semelhantes a outros estudos nacionais e internacionais (1,16,18) . Quanto aos tipos de câncer mais frequentes encontrados estão de acordo com as estimativas para o ano de 2011 (término da coleta de dados) e mantém-se semelhantes às estimativas para 2016 e 2017 no Brasil (19) .…”
Section: Discussionunclassified
“…Os pacientes do GI foram submetidos à terapia relaxamento com imagem guiada, conduzida por uma gravação em CD (16) , com duração de 15 minutos cada sessão. O CD inicialmente solicita ao paciente que se posicione confortavelmente, em seguida o conduz a realizar movimentos de respiração e relaxamento em diversas partes do corpo.…”
Section: Métodounclassified